The Influence of TikTok Social Media on Increasing Shoe Sales through Live Marketing - Dwi Kiki Enjela; Putri Arizka (Dinasti Publisher, 2026)
This study examines the effect of TikTok as a social media platform on shoe sales through live marketing. The rapid growth of social commerce has transformed consumer purchasing behavior, particularly through interactive video-based platforms. This research aims to analyze the role of TikTok in enhancing live marketing effectiveness and its impact on increasing shoe sales. The study adopts a quantitative approach using a survey method involving 165 TikTok Shop users in Desa Suka Maju, Kecamatan Kp. Lalang, Deli Serdang, North Sumatra. Data were analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that TikTok has a positive and significant effect on live marketing, and live marketing significantly influences shoe sales. These findings demonstrate that live marketing acts as a key mechanism in converting social media engagement into purchasing decisions. The study contributes to digital marketing management by providing empirical evidence on the strategic integration of social media content and live streaming to enhance sales performance in social commerce environments